1998
DOI: 10.1021/ac970608z
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of Polymer/Gas Partition Coefficients Calculated from Responses of Thickness Shear Mode and Surface Acoustic Wave Vapor Sensors

Abstract: Apparent partition coefficients, K, for the sorption of toluene by four different polymer thin films on thickness shear mode (TSM) and surface acoustic wave (SAW) devices are compared. The polymers examined were poly(isobutylene) (PIB), poly(epichlorohydrin) (PECH), poly(butadiene) (PBD), and poly(dimethylsiloxane) (PDMS). Independent data on partition coefficients for toluene in these polymers were compiled for comparison, and TSM sensor measurements were made using both oscillator and impedance analysis meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
70
0
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(75 citation statements)
references
References 19 publications
4
70
0
1
Order By: Relevance
“…The contribution of mass loading to the sensor response is well accepted in this field while the contribution of the viscoelastic property of polymer coating is still under investigation, even in gasphase sensors. 18,19,[25][26][27] Unfortunately, results in gas phase cannot be totally adapted or used to explain liquid-phase responses. For example, ongoing work in liquid-phase sensing has also shown that for a rubbery polymer such as PDMS viscoelasticity changes can clearly dominate sensor response.…”
Section: Mass Loading and Viscoelastic Contributions To Sensormentioning
confidence: 99%
See 1 more Smart Citation
“…The contribution of mass loading to the sensor response is well accepted in this field while the contribution of the viscoelastic property of polymer coating is still under investigation, even in gasphase sensors. 18,19,[25][26][27] Unfortunately, results in gas phase cannot be totally adapted or used to explain liquid-phase responses. For example, ongoing work in liquid-phase sensing has also shown that for a rubbery polymer such as PDMS viscoelasticity changes can clearly dominate sensor response.…”
Section: Mass Loading and Viscoelastic Contributions To Sensormentioning
confidence: 99%
“…This is consistent with reported amplification factors due to viscoelastic effects that are reported in the literature for gas-phase sensing, which are in the range of 2−4. 18,19,[25][26][27] Figure 6 Selectivity comparison of 0.64-μm PIB-coated guided SH-SAW sensor platform in the detection of toluene, xylenes, and ethylbenzene in DI water. -is the simulation result using predicted added mass loading and incremental viscoelastic changes based on experimental loss data.…”
mentioning
confidence: 99%
“…(1) is often insufficient for predicting the magnitude of sensor response [29][30][31][32][33]. Positive frequency shifts have also been observed for SAW devices coated with PDMS films and exposed to selected gas phase analytes [34][35][36].…”
mentioning
confidence: 99%
“…Taking m P /m A ≈ 500 (approximately the degree of polymerization) and γ = 1 we obtain m SAW = 1-7. For several analyte-polymer pairs the experimentally reported values are m SAW = 1.5-3.45 [32,34,35,37].…”
Section: Sensor Response and Its Relation To Partition Coefficientmentioning
confidence: 99%
“…(7) appears similar to the linear solvation energy relationship (LSER) for modeling vapor-polymer interaction under infinite dilution [3,29]. The LSER model has been widely used to explain equilibrium partition coefficients in gas-liquid chromatography (GLC), thermogravimetry (TG), and quartz crystal microbalance (QCM) and surface acoustic wave (SAW) sensing experiments [30][31][32][33][34][35]. In this model, each interaction term on the right of Eq.…”
Section: Theory Of Analyte Partitioningmentioning
confidence: 99%